Zoonotic potential of the Clostridium difficile RT078 family in Taiwan. (October 2016) - Tsai, Bo-Yang; Ko, Wen-Chien; Chen, Ter-Hsin; Wu, Ying-Chen; Lan, Po-Han; Chen, Yi-Hsuan; Hung, Yuan-Pin; Tsai, Pei-Jane
Abstract: Clostridium difficile is the major cause of nosocomial diarrhea. We have previously demonstrated that in southern Taiwan, severe C . difficile -associated diarrhea (CDAD) cases were due to the C . difficile RT 126 strain infection, indicating the arrival of an epidemic C . difficile clone in southern Taiwan. RT126 has a close genetic relationship with RT078. However, the RT078 family is the predominant strain of C . difficile in animals worldwide, particularly in swine. In this study, we surveyed C . difficile strains isolated from swine at several farms in Taiwan from August 2011 to March 2015. We found that all swine strains, namely RT078 (32.5%, 37 of 114), RT126 (28.9%, 33 of 114) and RT127 (37.7%, 43 of 114), belonged to the toxigenic RT078 family. All strains had high gyrA mutation rate (57.9%, 66/114), which was linked to quinolone resistance. Notably, Rep-PCR revealed that 3 RT078 animal strains had the same fingerprint as human RT078 clinical isolates; their phylogenic relationship was closely related to the whole gene sequences of tcdB, thus suggesting zoonotic potential for C . difficile infection in Taiwan. Highlights: All swine strains collected from different area of Taiwan, namely RT078, RT126 and RT127, belonged to the toxigenic RT078 family. These strains had high gyrA mutation rate which was linked to quinolone resistance. Genetic analysis revealed that 3 RT078 swine strains had the same fingerprint and closely phylogenic relationship as human RT078 clinical isolates. Here we suggest a zoonotic potential for Clostridium difficile infection between swine and human.